2018
DOI: 10.1007/s11244-017-0882-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Poisoning Resistance and Structural Stability of Single Atom Alloys

Abstract: Platinum group metals (PGMs) serve as highly active catalysts in a variety of heterogeneous chemical processes. Unfortunately, their high activity is accompanied by a high affinity for CO and thus, PGMs are susceptible to poisoning. Alloying PGMs with metals exhibiting lower affinity to CO could be an effective strategy toward preventing such poisoning. In this work, we use density functional theory to demonstrate this strategy, focusing on highly dilute alloys of PGMs (Pd, Pt, Rh, Ir and Ni) with poison resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
275
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(307 citation statements)
references
References 64 publications
19
275
3
2
Order By: Relevance
“…Chemical bonding between the constituents in alloys alters the valence electronic states that are responsible for the catalytic behavior of the metals. Experimental and theoretical works have shown that the unique isolated geometries of metals in SAA's can lead to electronic perturbations, which can in turn lead to changes in adsorption enthalpies and reaction barriers . To determine the effect of atomic ordering on the valence states of Pt, in situ RIXS measurements and DFT calculations were performed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chemical bonding between the constituents in alloys alters the valence electronic states that are responsible for the catalytic behavior of the metals. Experimental and theoretical works have shown that the unique isolated geometries of metals in SAA's can lead to electronic perturbations, which can in turn lead to changes in adsorption enthalpies and reaction barriers . To determine the effect of atomic ordering on the valence states of Pt, in situ RIXS measurements and DFT calculations were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and theoretical works have shown that the unique isolated geometries of metals in SAA's can lead to electronic perturbations, which can in turn lead to changes in adsorption enthalpies and reaction barriers. [12,27,[37][38][39] To determine the effect of atomic ordering on the valence states of Pt, in situ RIXS measurements and DFT calculations were performed. The 2-D RIXS planes show the incident photon energy (x-axis) and energy loss (y-axis) versus the intensity of emitted photons ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations